Ethnobotanical study of plants used by the traditional healers to treat malaria in Mogovolas district, northern Mozambique - Manuel, Leonardo (2020)
Malaria is an important parasitic disease that affects mostly the African continent. Traditional medicine is very important in Mozambique and traditional healers play a key role in the primary health care services, particularly in rural areas. We aim to report the results of an ethnobotanical survey undertaken in Mogovolas district, northern region of Mozambique. We recorded and identified the medicinal plants used by traditional healers for treatment of malaria, as well as the mode of preparation and administration.